2020
DOI: 10.1785/0120200112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microseismicity and Reactivated Fault Size to Assess the Potential for Felt Events by CO2 Injection in the Illinois Basin

Abstract: The results of monitoring of carbon dioxide (CO2) injection at the Illinois Basin—Decatur Project (IBDP) and the companion Illinois Industrial Carbon Capture and Sequestration Sources (IL-ICCS) project—have shown that reservoir response to fluid pressure changes can vary significantly at different injection locations within the same reservoir. Predrill reservoir characterization is important to identify potentially seismogenic faults. However, interpretations of newly reprocessed 3D seismic reflection data ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…A potential explanation for the reactivation of critically stressed fault patches in the basement is pressure communication through basement faults 11 , 12 . This explanation is consistent with a reduction in seismic activity at Decatur, when injection was shifted towards a shallower injection well, positioned above some shale baffles which are acting as barriers to fluid flow towards the basement faults 10 .…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…A potential explanation for the reactivation of critically stressed fault patches in the basement is pressure communication through basement faults 11 , 12 . This explanation is consistent with a reduction in seismic activity at Decatur, when injection was shifted towards a shallower injection well, positioned above some shale baffles which are acting as barriers to fluid flow towards the basement faults 10 .…”
Section: Introductionsupporting
confidence: 81%
“…In both Decatur and In Salah, microseismicity is strongly clustererd spatially. A high-resolution monitoring network at Decatur allowed to further reveal clear linear structures within the microseismic event clusters 7 and focal mechanisms 8 , which are correlating with the preferred fracture orientation arising from the known regional stress regime in the basement 9 , 10 . A potential explanation for the reactivation of critically stressed fault patches in the basement is pressure communication through basement faults 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The Stage 2C injection shares an important similarity to other CCS projects with documented seismicity: the seismogenic faults were only discovered post-injection in the plume images and/or induced seismicity aligned along the faults' surfaces (Dance et al, 2019;Harvey et al, 2021;Williams-Stroud et al, 2020;Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…The Stage 2C injection shares an important similarity to other CCS projects with documented seismicity: the seismogenic faults were only discovered post‐injection in the plume images and/or induced seismicity aligned along the faults’ surfaces (Dance et al., 2019; Harvey et al., 2021; Williams‐Stroud et al., 2020; Zhang et al., 2015). It is commonly believed that for most settings and relatively mild injection schedules, such undetectable faults are unlikely to serve as either leakage pathways or cause widely felt seismicity (Rutqvist et al., 2016).…”
Section: Discussionmentioning
confidence: 86%
“…Previous field demonstration projects revealed that the relatively small number and low magnitude of seismic events have been detected after injection operations (White & Foxall, 2016; Williams‐Stroud et al., 2020), suggesting that geological CO 2 storage is unlikely to pose a seismic hazard. However, the amounts of injected CO 2 have typically been small (less pressurization expected), and the difficulty in accurate subsurface monitoring also limits the accurate detection of seismic activities in spatial extent and/or temporal coverage (Kaven et al., 2015; Nicol et al., 2013).…”
Section: Introductionmentioning
confidence: 99%